Australian Marsh Beetles (Coleoptera: Scirtidae) 4. Two new genera, Austrocyphon and Tasmanocyphon - Zwick, Peter (Zootaxa, 2013)
The related new genera Austrocyphon and Tasmanocyphon are erected for 42 small Australian marsh beetles resembling members of the genus Cyphon Paykull in habitus. They are distinguished from Cyphon. Only males are known of most species but for two of them larvae and pupae are also available. Austrocyphon species occur in all Australian Federal States, and one species is Australasian and shared with Papua New Guinea. The following species are included: Austrocyphon acaciae sp. n., A. aculeatus sp. n., A. acustropicus sp. n., A. adelaidae (Blackburn), A. asper sp. n., A. bidens sp. n., A. bifidus sp. n., A. charon sp. n., A. crinitus (Klausnitzer), A. curvispina, sp. n., A. deserticola sp. n., A. doctus (Lea), A. enigmaticus sp. n., A. excisus sp. n., A. fenestratus (Blackburn), A. flagellifer sp. n., A. furcatus sp. n., A. hamatus sp. n., A. harpago sp. n., A. leptophallus sp. n., A. linguatus sp. n., A. lobatus sp. n., A. neptunus sp. n., A. noctua sp. n., A. ovensensis (Blackburn), A. papilio sp. n., A. perdoctus sp. n., A. pictus (Blackburn), A. quadridens sp. n., A. quinquespinosus sp. n., A. robustus sp. n., A. setifer sp. n., A. spiculifer sp. n., A. stylatus sp. n., A. stylifer sp. n., A. submersus sp. n., A. tinea sp. n., A. tomweiri sp. n., A. tribulator sp. n., A. tropicus sp. n., A. unguiculatus sp. n., A. wattsi sp. n. Tasmanocyphon is endemic to Tasmania, and only the adult male is known. The genus is monotypic, including only T. heideae, sp. n.